Impact of the COVID-19 Pandemic on Survival in the Patients With the Intra-Abdominal Infections - Gálvez-Benítez, Lydia; Rodríguez-Villodres, Ángel; Álvarez-Marín, Rocío; Jiménez-Rodríguez, Rosa; Lepe-Jiménez, José Antonio; Pachón, Jerónimo; Smani, Younes (Frontiers in Medicine, 2021)
To analyse the availability and access to hospital for patients with intraabdominal infections (IAI) by Escherichia coli as a result of COVID-19 pandemic, and the impact of these changes in the diagnosis and their effects on the death of these patients. Two prospective observational cohorts of patients with IAI by E. coli were conducted in 2016 (pre-COVID-19, N=108) and in 2020 (during COVID-19, N=96) at University Hospital of Seville, Spain. Demographic and clinical variables were collected and analysed. Patients were followed up during 120 days, until hospital discharge or death. Bivariate and multivariate analysis were performed. Both cohorts were homogeneous according to age, sex, emergency surgery cause, immunosuppression, neutropenia, acquisition type and previous intervention. Patients attended during COVID-19 had significantly higher Charlson index and more McCabe score, required more emergency surgery, and had more severe infections with higher rates of septic shock and sepsis and presence of additional care support, as nasogastric tube. They were diagnosed later; time intervals between symptoms onset (SO) to first medical contact or surgical intervention (SI), and between first medical contact to admission or SI were significantly higher. The death rates during COVID-19 and pre-COVID-19 were 16.7% and 6.5%, respectively (P=0.02). Finally, the multivariate analysis in both cohorts together identified patients diagnosed during COVID-19, longer period from SO to SI, septic shock and Charlson index as independent factors associated with death. This study showed the impact of COVID-19 pandemic on the clinical outcome and death due to IAI, with time extension between SO and SI.